Therapeutic dosage of isotretinoin in rats may influence orthodontic tooth movement - Ferreira, Mayra Fernanda [UNESP]; Botazzo Delbem, Alberto Carlos [UNESP]; Ervolino, Edilson [UNESP]; de Abreu Costa, Luy [UNESP]; Antoniali Silva, Cristina [UNESP]; Prando dos Santos, José Ricardo; de Mendonça, Marcos Rogério [UNESP] (Elsevier, 2024)
Objective Isotretinoin, also known as 13-cis-retinoic acid, is an isomer of tretinoin, the oxidized form of Vitamin A. Orthodontic tooth movement (OTM) is the result of a cascade of inflammatory responses stimulated by a physical element that is the force generated by orthodontic appliances. Isotretinoin is mainly used among adolescents and young adults, and coincidentally it is this age group that also undergoes orthodontic treatment. Materials and Methods Fifty-five animals were used, and they were randomly divided into 11 groups, containing 5 animals in each group. Group 1: Control; Group 2: OTM for 7 days; Group 3: OTM for 14 days; Group 4: Treated with isotretinoin for 14 days with a dosage of 7.5 mg/kg/day; Group 5: Treated with isotretinoin for 14 days with a dosage of 1.0 mg/kg/day; Group 6: Treated with isotretinoin for 21 days with a dosage of 7.5 mg/kg/day; Group 7: Treated with isotretinoin for 21 days with a dosage of 1.0 mg/kg/day; Group 8: Treated with isotretinoin for 14 days with a dosage of 7.5 mg/kg/day and undergoing OTM for 7 days; Group 9: Treated with isotretinoin for 14 days with a dosage of 1.0 mg/kg/day and undergoing OTM for 7 days; Group 10: Treated with isotretinoin for 21 days with a dosage of 7.5 mg/kg/day and undergoing OTM for 14 days; Group 11: Treated with isotretinoin for 21 days with a dosage of 1.0 mg/kg/day and undergoing OTM for 14 days. In Groups 8, 9, 10 and 11, the animals were treated with isotretinoin for 7 days before OTM and maintained during the movement period in the respective groups. Results There was a significant difference in microtomographic parameters, including Trabecular Volume (BV/TV), Trabecular Thickness (Tb.Th), Number of Trabeculae (Tb.N), and Trabecular Separation (Tb.Sp), between the groups. The group that received orthodontic force in conjunction with isotretinoin treatment at a dosage of 7.5 mg/kg/day exhibited lower tooth displacement over a period of 21 days and 14 days. Conclusion Isotretinoin caused a reduction in tooth displacement during OTM when administered at a dose of 7.5 mg/kg/day and isotretinoin did change the microtomographic parameters of treated animals.
Keywords: Acne; Bone remodeling; Drug response; Isotretinoin; Orthodontic tooth movement; Retinoids